Evaluation of artificial reef in Tioman Island - Hanapiah, Muhammad Faiz; Saad, Shahbudin (2012)
Artificial reef is defined as a man-made, underwater structure, typically built for the purpose of promoting marine life in areas of generally featureless bottom. It has long become alternative in order to alleviate human impact in coastal ecosystem and enhancing fisheries. This study evaluated artificial reefs in Tioman Island in terms of coral assemblages and colonization of other invertebrates and fish. Eleven sites of artificial reefs were surveyed in June 2012 and the locations of artificial reefs were determined by using side scan sonar. The survey consists of underwater photography and videography. Concrete Table reef exhibited the highest number of coral species with 60% coral colonization while Enviro Reef recorded the lowest with only 5% colonization. Most of the surface areas of artificial reef are being colonized by algae assemblages. Low number of species recorded for all artificial reefs indicated that the artificial reef structure were not preferable for invertebrates’ colonization. The number of fish species available related with the number of coral available on artificial reef. Concreted Table reef which has the highest number of coral species recorded high number of fish species. The availability of coral in the artificial reef might provide better nursery and feeding ground for fish to colonize this area.